Occurence of free gas and focused fluid systems in the Veslemøy High area, SW Barents Sea - Pless, Gustav (Universitetet i Tromsø, 2009)
The high-resolution 3D seismic survey EL0001 allowed to document the subsurface fluid migration system and fluid accumulations within Veslemøy High, SW Barents Sea. Fluids migrate both through Cretaceous and Tertiary sediments, but also through younger glacial sediments. Veslemøy High is a structurally isolated high at the Cretaceous and Tertiary levels bounded by N-S trending west-dipping normal faults. Cretaceous to Miocene sediments that consists of deep marine shales dominate in the older part and Plio-Pleistocene successions deposited by glaciomarine processes dominate in the upper part. Fluid accumulations are identified in L. Paleocene to E. Eocene sediments, and in Pliocene to Pleistocene sediments of glacial origin. An extensive high-seismic amplitude anomaly of 790 km2 appears to occur in a fan system within the eastern section of the 3D survey extending into Tromsø Basin. High and negative seismic amplitudes indicate appreciable gas accumulations within the fan. On the seafloor the existence of pockmarks suggest that pockmark formation most likely occurred after the ice-sheet retreat and thus between 15 ka and 12.5-11.5 ka. Pockmarks may represent fluid flow events from violent eruptions associated with deglaciation processes. Some evidence exists that gas may have been generated in deeper basins. Fluids migrated into Veslemøy High primarily along Plio-Pleistocene strata from Sørvestsnaget Basin in the west and along Creataceous-Paleogene strata from Tromsø Basin in the east. As the fluids reach the apex of Veslemøy High vertical migration through giant chimneys and along normal faults dominate. It is important to note that there is no geophysical evidence for fluid migration from Cretaceous sediments that lie directly below the high.